얼굴돌림 및 사시를 동반한 영아안진에서 Adjusted Kestenbaum 술식의 효과 - 박성은(Sung Eun Park); 한승한(Sueng-Han Han); 이종복(Jong Bok Lee); 한진우(Jinu Han) (Daihan angwa haghoi jabji, 2019)
목적: 얼굴돌림과 사시를 동반한 영아안진환자를 대상으로 adjusted Kestenbaum 술식을 시행하고 이상두위 및 사시의 교정 효과를 알아보고자 하였다. 대상과 방법: 1996년부터 2014년까지 신촌 세브란스병원에 내원한 얼굴돌림과 사시를 동반한 영아안진환자를 대상으로 2개 혹은 3개의 외안근을 조절하는 adjusted Kestenbaum 술식을 시행받은 12명의 환자를 후향적으로 수술 전후 사시각과 얼굴돌림의 호전 정도를 분석하였다. 결과: 모든 환자들은 된눈떨림(jerky nystagmus)과 이에 대한 보상적인 고개돌림 및 사시가 동반되었고, 12명 환자 중 외사시는 8명, 내사시는 4명이었다. 수술 당시 평균 나이는 12.5 ± 10.7세(range, 2-36세)였고, 수술 후 경과 관찰기간은 평균 17.8 ± 12.0개월(range, 7-43개월)이었으며, 12명 중 8명(66.7%)에서 수술 후 얼굴돌림 및 사시가 모두 교정되었다. 모든 환자에게서 얼굴돌림은 교정되었으나, 4명은 사시각이 10프리즘디옵터(prism diopters) 이내로 교정되지 않았다. 결론: Adjusted Kestenbaum 술식은 한 번의 수술로 67%의 환자에서 사시와 얼굴돌림을 모두 성공적으로 교정할 수 있었다. 또한 2개 혹은 3개의 직근을 사용하기 때문에 4개의 직근을 모두 수술하는 것보다 간단하며, 1, 2개의 외안근을 보존할 수 있어 큰 강점이 될 것으로 생각된다. Purpose: To investigate the effect of adjusted Kestenbaum surgery in patients with idiopathic infantile nystagmus who were affected by both strabismus and face turn. Methods: This retrospective consecutive case series included 12 patients with infantile nystagmus who had face turn and strabismus. All patients underwent adjusted Kestenbaum surgery between 1996 and 2014, and primary outcome measures were the postoperative degree of face turn and strabismus. Results: All patients had jerky nystagmus with compensatory face turn and strabismus. Of the 12 patients, eight patients were exotropes and four patients were esotropes. The mean age at surgery was 12.5 ± 10.7 years (range, 2-36 years). The mean postoperative follow-up was 17.8 ± 12.0 months (range, 7-43 months). Surgery was successful in eight (66.7%) out of 12 patients. Improvement of anomalous head posture was satisfactory in all patients, but an angle of deviation within 10 prism diopters was not achieved in four patients. Conclusions: Adjusted Kestenbaum surgery simultaneously improved both ocular misalignment and face turn with one-stage surgery. Two or three rectus muscles surgery can be considered in these patients because it is not only simpler than four muscles surgery but also can preserve one or two rectus muscles. KCI Citation Count: 0